Photophysical properties of CdSe quantum dot self-assemblies with zinc phthalocyanines and azaphthalocyanines - Suchánek, Jan; Lang, Kamil; Novakova, Veronika; Zimcik, Petr; Zelinger, Zdeněk; Kubát, Pavel (Photochemical & photobiological sciences, 2013)
The formation of self-assemblies between CdSe quantum dots (QDs) and Zn phthalocyanines (Pc) and azaphthalocyanines (AzaPc) bearing alkylsulfanyl substituents and the photophysical properties of these assemblies were studied using both steady-state and time-resolved luminescence/absorption spectroscopy. The formation of the self-assemblies was accompanied by a blue shift of the Q band of the dyes and by a quenching of the CdSe QDs luminescence. The largest spectral shift of the Q-band was approximately 7 nm and was observed for pentan-3-ylsulfanyl-functionalised phthalocyanine (). Assuming a 1 : 1 stoichiometry, the calculated binding constant was 4 × 10(4) M(-1). Pc substituted with the bulky tert-butylsulfanyl groups (1) exhibited a smaller shift of the Q band. The quenching of the CdSe QDs luminescence by 1 was more effective than that observed for 3. The results indicated that the luminescence quenching may be due to a photoinduced charge transfer between 1 or 3 and the CdSe QDs. In contrast, the AzaPc (2) with the same substituents as 1 had little effect on the QDs luminescence. For all cases, we found an inefficient resonance energy transfer between the attached dyes and the CdSe QD. The formation of the self-assemblies had negligible effects on the photogeneration of the singlet oxygen, O2((1)Δg), that was fully controlled only by the absorption of the light by the macrocycles.
Keywords: Indoles; Organometallic Compounds; velikost částic; indoly; Quantum Theory; Solvents; Particle Size; organokovové sloučeniny; Selenium Compounds; Cadmium Compounds; Isoindoles; sloučeniny zinku; fluorescenční spektrometrie; sloučeniny selenu; rozpouštědla; Quantum Dots; isoindoly; kvantové tečky; Zinc Compounds; kvantová teorie; Spectrometry, Fluorescence; sloučeniny kadmia